New homodinuclear tris(3‐alkylpyrazolyl)borate complexes of CoII and NiII with a tetraacetylethane dianion as a bridging ligand. Issue 11 (6th October 2016) - Mikhalyova, Elena A.; Trofimenko, Swiatoslaw; Zeller, Matthias; Addison, Anthony W.; Pavlishchuk, Vitaly V.
Abstract : Two new homodinuclear tris(3‐alkylpyrazolyl)borate complexes of Co II and Ni II with a tetraacetylethane dianion as the bridging ligand were synthesized and characterized by mass spectrometry and X‐ray crystallography. A significant deviation from orthogonality between the acetylacetonate planes was observed in the two complexes. Abstract : Polynuclear complexes and coordination polymers of 3 d metals have attracted significant interest evoked by a number of their unique properties. One of the most common approaches to the directed synthesis of coordination polymers is the linking of pre‐prepared discrete coordination units by polydentate ligands. The formation of polynuclear complexes is usually a spontaneous process and precise prediction of the products of such reactions is virtually impossible in most cases. Tris(pyrazolyl)borates (Tp) act as tripodal `capping' ligands which form stable complexes with 3 d metal ions. In such 1:1 compounds, three metal‐ion coordination sites are occupied by N atoms from a Tp anion. This limits the number of remaining coordination sites, and thus the number of additional ligands which may coordinate, and opens an attractive approach for the directed design of desirable structures by exploiting ligands with appropriate composition and topology. In the present study, Tp anions with neopentyl [Tp Np, tris(3‐neopentylpyrazolyl)borate] and cyclohexyl [Tp Cy, tris(3‐cyclohexylpyrazolyl)borate] substituents were used as `capping' ligands and the dianion of tetraacetylethane (3, 4‐diacetylhexa‐2, 4‐diene‐2, 5‐diolate, tae 2− ) was employed as a bridge. The dinuclear complexes (μ‐3, 4‐diacetylhexa‐2, 4‐diene‐2, 5‐diolato‐κ 4 O 2, O 3 : O 4, O 5 )bis{[tris(3‐cyclohexyl‐1 H ‐pyrazol‐1‐yl‐κ N 2 )borato]cobalt(II)} acetonitrile disolvate, [Co2 (C27 H40 BN6 )2 (C10 H12 O4 )]·2CH3 CN, (I)·2CH3 CN, and (μ‐3, 4‐diacetylhexa‐2, 4‐diene‐2, 5‐diolato‐κ 4 O 2, O 3 : O 4, O 5 )bis{[tris(3‐neopentyl‐1 H ‐pyrazol‐1‐yl‐κ N 2 )borato]nickel(II)}, [Ni2 (C24 H40 BN6 )2 (C10 H12 O4 )], (II), were synthesized by the reaction of the mononuclear complexes Tp Cy CoCl or Tp Np NiCl with H2 tae (3, 4‐diacetylhexane‐2, 5‐dione or tetraacetylethane) in the presence of NEt3 as base. Compounds (I) and (II) were characterized by mass spectrometry, elemental analysis, and X‐ray crystallography. They possess similar molecular structures, X‐ray diffraction revealing them to be dinuclear in nature and composed of discrete Tp– M units in which two metal ions are linked by a tae 2− dianion. Each metal ion possesses a five‐coordinate square‐pyramidal environment. The interplanar angles between the acetylacetonate fragments are significantly smaller than the near‐90° values commonly observed.